Pengaruh Pengalaman Nasabah dan Kepuasan Nasabah terhadap Loyalitas Nasabah PT Bank Permata TBK - Andre Winarto; Richard Andrew (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the relationship between customer experience, customer satisfaction, and customer loyalty at PT Bank Permata Tbk. In an increasingly competitive banking industry, customer experience has become a critical factor influencing customers' perceptions of bank services. A positive experience can enhance customer satisfaction, which ultimately contributes to their loyalty to the banking institution. This research employs a quantitative method using a survey of 100 customers of PT Bank Permata Tbk. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that customer experience has a positive and significant impact on customer loyalty, and customer satisfaction also positively and significantly affects customer loyalty. However, no mediating effect was found of customer satisfaction on the relationship between customer experience and customer loyalty.